miR-491 Inhibits Osteosarcoma Lung Metastasis and Chemoresistance by Targeting αB-crystallin - Wang, Shu-Nan; Luo, Song; Liu, Chang; Piao, Zhenghao; Gou, Wenlong; Wang, Yun; Guan, Wei; Li, Qing; Zou, Hua; Yang, Zhen-Zhou; Wang, Dong; Wang, Yan; et al. (Molecular therapy, 2017)
Dysregulated microRNAs (miRNAs) play an important role in osteosarcoma (OS) progression. In the present study, we investigate the clinical significance of serum miR-491 level and the potential role of miR-491 in OS lung metastasis and chemoresistance. Clinical data show that the level of miR-491 was decreased in serum from OS patients compared with healthy control subjects, and that a decreased serum miR-491 level is correlated with increased metastasis, poor chemoresponse, and lower survival rate in OS patients. In vitro and in vivo experiments show that overexpression of miR-491 suppresses OS cell lung metastasis, whereas it enhances cisplatin (CDDP)-induced tumor growth inhibition and apoptosis. In contrast, inhibition of miR-491 stimulates OS cell lung metastasis and suppresses CDDP-induced tumor growth inhibition and apoptosis. Furthermore, we demonstrate that miR-491 exerts its role by directly targeting αB-crystallin (CRYAB) in OS. Our findings suggest that serum level of miR-491 has potential as a biomarker for predicting OS progression and prognosis of OS patients. Additionally, restoration of miR-491 may be a novel strategy for inhibiting OS lung metastasis and overcoming OS cell resistance to chemotherapy. Wang et al. show that suppressed expression of miR-491 contributes to osteosarcoma (OS) lung metastasis and chemoresistance. In contrast, overexpression of miR-491 can inhibit OS lung metastasis and overcome chemoresistance, suggesting restoration of miR-491 is a novel strategy for treatment of OS lung metastasis and chemoresistance.